Securing Land Transactions with Biometric data in Ghana - Samuel Boamah Asiedu (African Journal on Land Policy and Geospatial Sciences, 2020)
There is a gap between land tenure and the physical land giving room for impersonation, multiple allocation and sale of plots, loss of possession, land racketeering and fraud through forgery. Hence, the need to identify unambiguously parties involved in land transactions so that the root of title can be traced to ensure tenure security. This paper explores innovative ways of filling the gap with biometric data to secure land transactions. Through interviews and self-administered questionnaire with google forms, and snowball sampling technique, perception of participants across Ghana were assessed on what constitutes secure land transaction. The researchers also assessed participants’ knowledge of biometric systems and their acceptability in recording biological traits of grantors and grantees in land transactions. Most participants were conversant with the use of biometric systems and were optimistic that its use might bring sanity in land transactions and enhance the security of tenure in Ghana.